Awareness regarding weaning and its associated factors among mothers in rural Sindh - Ahsan Ali Dahani; Syed Imtiaz Ahmed Jafry; Syed Muhammad Zulfiqar Hyder Naqvi; Munir Ahmed Shaikh; Muhammad Zafar Iqbal Hydrie; Muhammad Zahid Shah (KARACHI MEDICAL AND DENTAL COLLEGE, 2020)
Objective: To determine the awareness regarding weaning and its associated factors among mothers in Kashmore, rural Sindh. Methods: A cross-sectional study was conducted among infant's mothers regarding awareness for weaning at Kashmore, a rural community in interior Sindh, from March 2108 to November 2018. The inclusion criteria were age of mothers 30 years or above and child's age more than two years whereas mothers refusing to give verbal informed consent were excluded from the study. A total of 200 mothers were included in the study and were interviewed by using a questionnaire designed specifically for the study. Data were analyzed using statistical package for social sciences version 20 while Mann Whitney U test and Kruskal Wallis H test were used for inferential analysis. The study duration spanned over 9 months. Results: The mean age of the mothers was 27.1 ± 6.3 years and the average number of children for every household was 2.4 ± 1.3. When participants were asked about what weaning foods should be given to assess their awareness, 176 (88.0%) mothers said bread or roti, 153 (76.5%) said yogurt, 144 (72%) said boiled rice, 133 (66.5%) said vegetables, 130 (55.0%) said suji or kheer, 95 (47.5%) said egg yolk while only 71 (35.5%) said fruits. The study results further showed that among the socio-demographic characteristics compared the mean awareness scores of the mothers were significantly different across categories of mothers' education (p<0.001), fathers' education (p<0.001), monthly household income (p<0.001) and type of family (p=0.025). Conclusion: Based on study results it can be concluded that certain socio-demographic factors influence the awareness of the mothers regarding the weaning of their children. Therefore any effort aimed at improving their awareness should take into account the factors identified in this study.